Legal Study on Traffic Violations Committed by School Children at Bangko Police Traffic Unit - Siagian, Chandra; Pakpahan, Zainal Abidin; Siahaan, Nimrot (International Journal Labs, 2024)
Traffic violations are committed not only on adults, even including the age of children also commit many traffic violations. Legal sanctions for violators will be imposed, both administrative criminal sanctions and imprisonment sanctions. Juridically, violators will be subject to imprisonment for a maximum of 1 (one) year and/or a maximum fine of IDR 2,000,000.00 (two million rupiah) in accordance with Article 229 paragraph (3) of Law Number 22 of 2009 concerning Road Traffic and Transportation. The law imposes imprisonment, confinement and fines for traffic violations in the Bangko police station. In addition, criminals and perpetrators of traffic violations can be sentenced to additional crimes in the form of revocation of driver's licenses or compensation for losses caused by criminal acts or traffic violations, but this enforcement is intended for traffic offenders who are adults. Meanwhile, criminal liability for perpetrators of traffic violations committed by school children in the jurisdiction of the Bangko Police Station, usually first looks at the elements, namely intentional or not or negligence that results in the occurrence of the violation, it will affect the legal action that will be taken by the Bangko Police Station for traffic violators. For criminal law liability for traffic violations committed by school children in the jurisdiction of Bangko Police Station, violators of the age category of school children are only given criminal sanctions in accordance with applicable legal provisions.